COMPARISON OF TROPONIN T AND ENZYME LEVELS IN ACUTE MYOCARDIAL INFARCTION AND SKELETAL MUSCLE INJURY - Majeed, Rehan; Jaleel, Anila; Siddiqui, Imran A.; Sandila, Pervaiz; Baseer, Abdul (Journal of Ayub Medical College Abbottabad, 2007)
Background: The objective of this study was to compare the levels of troponin T and enzymes levels in myocardial infarction and skeletal muscle injury. Methods: This study was carried out at Basic Medical Sciences Institute, JPMC Karachi, Pakistan. Ninety subjects were selected. Thirty controls, thirty patients suffering from myocardial infarction and thirty suffering from skeletal muscle injury were selected from National Institute of Cardiovascular Diseases. Creatine kinase, aspartate amino-transferase, lactate dehydrogenase and Troponin T were determined by kit methods. Results: Troponin T level rises significantly (p<0.01) in patients suffering from myocardial infarction. Creatine kinase (CK), CKMB, aspartate aminotransferase and lactate dehydrogenase levels rises significantly (p<0.01) in both groups compared with controls. Conclusion: Troponin T is an early indicator of myocardial infarction and is superior to CKMB in diagnosis of myocardial injury. There is no increase in troponin T levels in skeletal muscle injury. Key words: Troponin T, Acute, Myocardial infarction, Skeletal, muscle, injuries